SARS-CoV-2: a clinical update - da Silveira Cespedes, Mateus (2020)
INTRODUCTION: The covid-19 pandemic decreed by WHO raises greater knowledge about it. EPIDEMIOLOGY: The infection reached the mark of 950,000 patients in 33 countries and raised as risk factors the presence of comorbidities and advanced age. TRANSMISSIBILITY: The transmissibility calculated so far is similar to the H1N1 epidemic, however with a lower mortality rate. PHYSIOPATHOLOGY: The SARS-CoV-2 virus, of the Coronaviridae family, has the capacity for cellular invasion through the angiotensin-converting enzyme 2 present in the lower respiratory epithelium and in the cells of the small intestine mucosa. CLINICAL MANIFESTATIONS: the presentation can be divided into mild (fever, fatigue, cough, myalgia and sputum) and severe (cyanosis, dyspnoea, tachypnea, chest pain, hypoxemia and need for mechanical ventilation) and has an estimated mortality of just over 2% . DIAGNOSIS: it occurs through the detection of viral load in the CRP-TR of patients with high clinical suspicion. TREATMENT: based on supportive and infection control measures. In severe cases, the use of medications such as hydroxychloroquine and azithromycin or remdesevir can be promising. Take care to avoid the use of corticosteroids. There is insufficient evidence to refrain from using ibuprofen and ACE inhibitors / BRAs.